2005
DOI: 10.1248/bpb.28.1229
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis Stimulation in Murine B16 Melanoma Cells by Umberiferae Plant Extracts and Their Coumarin Constituents

Abstract: Gray hair is caused by a genetic predisposition, aging, decrement of melanocytes by environmental stress, and decrement of the biosynthesis of melanin pigment or melanogenesis.1,2) Hair dye agents are used for the treatment of gray hair. However, there remain some problems with these agents, such as side effects due to the dyes. Thus, there is a need for anti-gray hair agents that exhibit satisfactory melanogenesis activity and gray hair prevention. For the development of gray hair prevention agents, we have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 13 publications
(31 reference statements)
1
30
0
1
Order By: Relevance
“…The flavone quercetin, originally described as a tyrosinase inhibitor [121], turned out to be a strong inducer of melanogenesis in vitro [122]. Although some hydroxylated derivatives of coumarins were reported to inhibit melanogenesis [123], several coumarins of seven umberiferae plants stimulated melanogenesis in murine melanoma cells [124]. The number of putative hypo-or hyper-pigmenting agents is vast, but promising effects detected in vitro are often not confirmed in clinical tests.…”
Section: Challenges For the Futurementioning
confidence: 99%
“…The flavone quercetin, originally described as a tyrosinase inhibitor [121], turned out to be a strong inducer of melanogenesis in vitro [122]. Although some hydroxylated derivatives of coumarins were reported to inhibit melanogenesis [123], several coumarins of seven umberiferae plants stimulated melanogenesis in murine melanoma cells [124]. The number of putative hypo-or hyper-pigmenting agents is vast, but promising effects detected in vitro are often not confirmed in clinical tests.…”
Section: Challenges For the Futurementioning
confidence: 99%
“…3,4) Therefore, it was expected that agents which exhibit both melanogenesis stimulation activity and testosterone 5a-reductase inhibitory activity may be desirable ingredients of hair-care cosmetic products for prevention of gray hair and alopecia. During the course of our screening program using cultured murine B16 melanoma cells for the development of gray hair prevention agents from natural resources, we found that extracts of some Piper species (Piperaceae) showed a potent stimulation effect on melanogenesis without any effects on cell proliferation, and two lignans, (Ϫ)-cubebin (1) and (Ϫ)-3,4-dimethoxy-3,4-desmethylenedioxycubebin (2), were isolated as active constituents from the leaves of Piper nigrum L. [5][6][7] With the expectation that we might find new desirable agents from Piper species to prevent gray hair and alopecia as described above, the testosterone 5a-reductase inhibitory activity of 50% ethanolic extracts obtained from several different parts of six Piper species (P. nigrum L., P. methysticum FORST., P. betle L., P. kadsura (CHOISY) OHWI, P. longum L., and P. cubeba L.) was examined. This paper deals with the screening results of in vitro testosterone 5a-reductase inhibitory activity of Piper species, the activity-guided fractionation of P. nigrum leaf extract led to the isolation of active lignans, 1 and 2, and the in vivo anti-androgenic activity of the leaf extract.…”
mentioning
confidence: 99%
“…Among the Angelica species, coumarin derivatives extracted from Angelica dahurica have been reported to stimulate (29) or inhibit melanogenesis (30). In the case of Angelica sinensis, melanogenesis was stimulated (31).…”
Section: Discussionmentioning
confidence: 99%